FUNGSI, KEDUDUKANDAN PERBANDINGAN HADITS DENGAN AL- QUR’AN - Abdul Wahab Syakhrani; Ahmad Fahri (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
The science of hadith is the science that discusses the rules to determine the position of sanad and matan, whether accepted or rejected. According to Tengku Muhammad Hasbi AshShiddieqy: "Hadith science, namely knowledge related to hadith, has many kinds." According to Izzudin Ibnu Jamaah: "Science of hadith is the science of basic rules to find out the condition of a sanad or matan (hadith). The important goal of studying hadith is to know (sort out) authentic hadiths from others. Namely knowing the circumstances of a hadith, whether the hadith is authentic, hasan, or even da'if (weak, so it cannot be used as a guide). The person who first made this ulumul hadith, namely his name, was Muhammad bin Muslim bin Abdillah bin Syihab Az-Zuhri. He was the first to record and collect them on the orders of Caliph Umar bin Abdul Aziz. The function of the hadith to the Al Quran is as Bayan At-Tafsir, as Bayan At-Tafsir, as Bayan At-tasyri', and as Bayan Nasakh. The position of the Hadith as a bayani or carrying out the function of explaining the law of the Koran is beyond doubt and can be accepted by all parties, because that is what Allah SWT assigned the Prophet to do. However, in the position of hadith as a proposition that stands alone and as a second source after the Al-Quran